Unveiling Patience: The Intersection of the Qur'an and Hadith in Buya Hamka’s Thought - Langaji, Abbas; Ilham, M.; Syatar, Abdul; Karim, Abdul Rahim; Rusdiansyah, Rusdiansyah (Universitas Islam Negeri Mataram, 2024)
This article examines the concept of patience in the thought of Buya Hamka, focusing on the integration between the Qur’an and hadith in Tafsir Al-Azhar. As a central theme in Islam, patience is not only understood as a passive reaction to adversity but as an active attitude reflecting spiritual strength and depth of faith. This article identifies how Buya Hamka interprets patience through the bi al-ma’thūr method, using hadith as an explanatory tool to deepen the meaning of patience-related verses. With a qualitative analysis that emphasizes textual study, this article presents evidence that Buya Hamka relates patience to social and individual contexts and creates practical guidance for Muslims in facing the challenges of daily life. Through this approach, the author shows how patience can serve as a tool to achieve emotional balance and mental resilience. The contribution of this study lies in the emphasis on the relevance of Hamka’s tafsir in the modern context, as well as the functionalization of hadith in expressing the profound values of patience. By filling an existing academic gap, this research offers new insights into the relationship between historical Islamic texts and contemporary spiritual practices, making Tafsir Al-Azhar an essential resource in guiding Muslims to understand and apply patience in their lives.